Catch the Wahine and Win: (Re) Addressing the Polynesian - Christiansen, Lurlene (Auckland University of Technology, 2003)
This exegesis investigates the historical practice of re-producing stereotypical spectacles of “Polynesian” women through the medium of photography and, compares and contrasts the continuing shaping of Pacific Island identities through contemporary practices in today’s world. In so doing, it singles out the homogenous aspects of colonialism's cultural practices and distinguishes their continuities in neo-colonial mass-media culture. This recurrence of colonial ideologies and practices is specifically evident in popular culture magazines, television and the internet. I argue that photographs and spectacles, both historical and modern, that were and are now used under the pretext of and directed toward naturalising the precept of colonialism, constitute imagery that continues to dis-empower Pacific Island women today. They cause one to question notions of personal and social identity. While this project is in theory an objective analysis, this project equally focuses on subjectivity and imagery of racial and cultural difference that has shaped our immediate past and continues to shape our present identities. Written from a Samoan woman’s perspective, from one who exists in a mediascape arena as “marketable Other”, this paper will be of interest to artists, scholars, students and researchers for whom issues of identity, subjectivity and power are of identifiable importance.
Keywords: Polynesian women; Polynesians; Pacific Islanders in art; Pacific Islanders